Allelic Ratio of KRAS Mutations in Pancreatic Cancer. (16th March 2015) - Lennerz, Jochen K.; Stenzinger, Albrecht
Abstract : KRAS is not simply mutated or wild type in pancreatic ductal adenocarcinoma (PDAC); actually, it has never been. More than 90% of PDACs carry mutated KRAS alleles; however, the impact on PDAC biology may vary with the tumor‐specific allelic ratio and dosage of mutated KRAS .